Attention to women in the situation of sexual violence in the bioethics perspective - Trentin, Daiane; de Oliveira Vargas, Mara Ambrosina; Pires de Pires, Denise Elvira; Hellmann, Fernando; Brehmer, Laura; Cézar Leal, Sandra (Acta Bioethica, 2018)
A qualitative, exploratory and analytical study, with the objective of investigating how the professionals approach the women in situations of sexual violence, from the perspective of Bioethics of Intervention. The study was carried out with the members of the multiprofessional and intersectoral team that provide care to women in situations of sexual violence in a municipality located in the central-north region of Rio Grande do Sul, Brazil. Data collection was performed through a semistructured interview between January and April 2016. The sample consisted of 30 professionals, including lawyer, social worker, nurse, doctor, psychologist and other professionals of the team. Data analysis was guided by the Thematic Content Analysis. The results were organized into five categories: Professional commitment; Attendance beyond the professional scope; Team work; Intersectoriality and professional instrumentalization. The multiprofessional team has difficulties in the attention because the places of attendance are not adequate and the amount of professionals to attend integrally is insufficient. There are also professionals unprepared for this type of care. Other problems are the underreporting of cases and the personal difficulties of professionals in addressing victims of sexual violence. Bioethics of Intervention supports interventions to transform reality and improve care for women in situations of sexual violence. It is necessary to implement public policies and laws to protect women and invest in continuing education of professionals. These strategies can overcome difficulties and improve the quality of care.